Francesco d’Assisi e i suoi frati come predicatori: forme e contenuti della predicazione nel Duecento - Aleksander Horowski (Artes)
The paper analyzes Francis of Assisi’s preaching in light of his writings and Medieval biographical sources, comparing it to the ars praedicandi of the time. Emphasis is placed on the evolution of both the content of his proclamation and the form through which the Christian message is transmitted, while also pinpointing some of the suggestions the Assisiate formulated for his friars in terms of preaching. One of the key moments of transformation in the kind of preaching Francis performed coincided with his taking on holy orders, that is, becoming a deacon, and the gradual acquisition of basic theological scholarship, an education obtained in part by listening to liturgical texts